Structural parameter identification of a bolted connection embedded with a piezoelectric interface - Huynh, Thanh-Canh (Vietnam Journal of Mechanics, 2020)
As the impedance-based technique has been commonly accepted as an innovative structural health monitoring tool, structural identification of a piezoelectric-driven system is of significant interest for damage identification and quantification. This study presents a predictive modelling strategy, which combines the finite element (FE) method with a model-updating approach, for estimating the structural parameters of a piezoelectric interface-bolted connection system. Firstly, the basic operating principle of the piezoelectric-based smart interface is introduced. Secondly, a bolted connection is selected as a host structure to conduct real impedance measurement via the smart interface. Thirdly, a numerical FE model corresponding to the experimental model is established by using a FE program, COMSOL Multiphysics. A sensitivity-based model updating algorithm is adopted to fine-tune the FE model. Finally, structural parameters of the FE model are determined as the numerical impedance signatures match with the measured ones at the same high-frequency band with identical patterns. This study is expected to open an alternative approach for determining unknown structural parameters of the piezoelectric interface-bolted joint system in practice.